When Viruses Play Team Sports: Mixed Infections in Plants - Moreno, Ana Beatriz; López-Moya, Juan José (Phytopathology, 2020)
The pathological importance of mixed viral infections in plants might be underestimated except for a few well-characterized synergistic combinations in certain crops. Considering that the host ranges of many viruses often overlap and that most plant species can be infected by several unrelated viruses, it is not surprising to find more than one virus simultaneously in the same plant. Furthermore, dispersal of the majority of plant viruses relies on efficient transmission mechanisms mediated by vector organisms, mainly but not exclusively insects, which can contribute to the occurrence of multiple infections in the same plant. Recent work using different experimental approaches has shown that mixed viral infections can be remarkably frequent, up to the point that they could be considered the rule more than the exception. The purpose of this review is to describe the impact of multiple infections not only on the participating viruses themselves but also on their vectors and on the common host. From this standpoint, mixed infections arise as complex events that involve several cross-interacting players, and they consequently require a more general perspective than the analysis of single-virus/single-host approaches for a full understanding of their relevance.